The effect of the enhanced recovery after surgery program on radical cystectomy: a meta-analysis and systematic review - Zhou, Yongheng; Li, Rongyang; Liu, Zhifeng; Qi, Wenqiang; Lv, Guangda; Zhong, Minglei; Liu, Xigao; Zhu, Meikai; Jiang, Zhiwen; Chen, Shouzhen; Shi, Benkang; Zhu, Yaofeng (Frontiers in Surgery, 2023)
Background: Bladder cancer (BCa) is the ninth most common malignant tumor worldwide. As an effective evidence-based multidisciplinary protocol, the enhanced recovery after surgery (ERAS) program is practiced in many surgical disciplines. However, the function of ERAS after radical cystectomy remains controversial. This systematic review and meta-analysis aimed to research the impact of ERAS on radical cystectomy. Methods: A systematic literature search of PubMed, EMBASE, SCOPUS and the Cochrane Library databases till April 2022 was conducted to identify the studies that performed the ERAS program in the radical cystectomy. Studies were selected, data extraction was performed independently by 2 reviewers, and quality was assessed. Using a random effects model to calculate the overall effect size. Odd ratio and standardized mean difference (SMD) with 95% confidence interval (CI) were conducted as the summary statistics for meta-analysis. Sensitivity analysis was subsequently performed. Result: Totals of 25 studies with 4083 patients were enrolled. The meta-analysis showed that the complications (OR =0.76; 95% CI: 0.63 to 0.90), the transfusion rate (OR=0.59; 95% CI: 0.39 to 0.90), readmission rate (OR=0.79; 95% CI: 0.64 to 0.96), LOS (SMD =−0.79; 95% CI: −1.41 to −0.17) and the time to first flatus (SMD =−1.16; 95% CI: −1.58 to −0.74) was significantly reduced in ERAS group. No significance was found in 90-day mortality and urine leakage. Conclusion: The ERAS program for radical cystectomy can effective decrease the risk of overall complications, postoperative ileus, readmission rate, transfusion rate, length of stay and time to first flatus who experienced radical cystectomy with relative safety.